Context-Based Chemistry Learning: A Systematic Literature Review - Minata, Zelen Surya; Rahayu, Sri; Dasna, I Wayan (FKIP Universitas Lampung, 2022)
This study aimed to examine the impact of context-based chemistry learning on cognitive, affective, psychomotor, and social aspects of students, integration of context-based learning with chemistry learning models or strategies, and implementation of effective context based chemistry learning. A total of 34 articles for further analysis were obtained from SCOPUS, ERIC, and Google Scholar database through systematic literature (SLR) method. The result of analysis showed that (1) context-based chemistry learning has a positive effect improving student’s cognitive, affective, psychomotor, and social aspects, (2) context-based chemistry learning can be integrated with certain learning models or strategies and presentation of learning context carried out at the beginning of learning, (3) the implementation of effective context-based chemistry learning can be done by considering several aspects including the selection of appropriate and applicable learning contexts, teacher master the concepts of learning materials and students actively participated in each learning syntax that is applied.Keywords: context-based learning, chemistry learning, systematic literature review.DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1446-1463